Pengembangan Media Pembelajaran Matematika Berbasis Website Dengan Pendekatan Kontekstual - Baihaqi, Rizal Baihaqi; Wulantina, Endah (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to develop a website-based learning media with a valid and interesting contextual approach.  The research method used is Research And Development (R&D) with a 4D development model which includes 4 stages, namely define, design, development and disseminate.  The location of this research is at MTs Ma'arif 23 Sendang Agung.  The subjects in this study were class VIII students at MTs Ma'arif 23 Sendang Agung, totaling 24 students.  The material developed is a flat sided space build material.  The results of this study indicate that the product developed based on the validation of media experts obtains a percentage of 68% with the "valid" criteria and the validation of material experts obtains a percentage of 90.5% with the criteria of "very valid".  Furthermore, the results of students' responses to the attractiveness of the developed media obtained a percentage of 83.41% with the criteria of "very interesting".  Based on these results it can be concluded that the website-based mathematics learning media with the contextual approach developed is valid and interesting so that it can be used in the learning process. Keywords : Contextual Approach, Learning Website, Mathematics